Key Economic Policy Developments in 2007–2015 and Challenges Ahead - Adam Czerniak; Ryszard Rapacki (Poland. Competitiveness Report 2016. The Role of Economic Policy and Institutions, 2016)
This chapter seeks to assess the main thrusts of Polish economic policy from 2007 to 2015, a period when the governing coalition of the Civic Platform (PO) and the Polish People's Party (PSL) was in power, with a focus on measures designed to boost growth and streamline the country's public finances in 2010–2015. After a sea change in Polish politics in the wake of the presidential and parliamentary elections in 2015, we also attempt to sum up the track record of the previous ruling coalition, which governed the country for eight years. At the same time, this chapter looks at the conditions in which the government formed by the conservative Law and Justice (PiS) party started its work, outlining the most important economic policy challenges for this new government.
Keywords: E61; E62; E63; 330; economic policy; fiscal policy; institutions; economic growth